Photocatalytic and Electrocatalytic Generation of Hydrogen Peroxide: Principles, Catalyst Design and Performance - Guo, Yan; Tong, Xili; Yang, Nianjun (Nano-Micro Letters, 2023)
Hydrogen peroxide (H2O2) is a high-demand organic chemical reagent and has been widely used in various modern industrial applications. Currently, the prominent method for the preparation of H2O2 is the anthraquinone oxidation. Unfortunately, it is not conducive to economic and sustainable development since it is a complex process and involves unfriendly environment and potential hazards. In this context, numerous approaches have been developed to synthesize H2O2. Among them, photo/electro-catalytic ones are considered as two of the most promising manners for on-site synthesis of H2O2. These alternatives are sustainable in that only water or O2 is required. Namely, water oxidation (WOR) or oxygen reduction (ORR) reactions can be further coupled with clean and sustainable energy. For photo/electro-catalytic reactions for H2O2 generation, the design of the catalysts is extremely important and has been extensively conducted with an aim to obtain ultimate catalytic performance. This article overviews the basic principles of WOR and ORR, followed by the summary of recent progresses and achievements on the design and performance of various photo/electro-catalysts for H2O2 generation. The related mechanisms for these approaches are highlighted from theoretical and experimental aspects. Scientific challenges and opportunities of engineering photo/electro-catalysts for H2O2 generation are also outlined and discussed. Highlights: 1 Basic principles of photo- and electro-catalytic hydrogen peroxide generation. 2 Recent progresses on the design, performance and mechanisms of photo- and electro-catalysts for hydrogen peroxide generation. 3 Scientific challenges and prospects of engineering photo- and electro-catalysts for hydrogen peroxide production.